Consumer Sentiment Analysis of Sustainable Branding in Modern Marketing: Perspectives from the Food and Beverage Industry - Yassir; Rafikah, Syarifah (Yayasan Pendidikan Belajar Berdikari, 2024)
This study aims to evaluate the impact of digital marketing strategies on consumer purchasing decisions in the retail industry in Bandung City, focusing on consumer sentiment towards sustainable branding. The results of linear regression analysis show that SCBB has a coefficient of 0.710, which means that every one unit increase in SCBB will increase the value of KP by 0.710 units. The t test shows that SCBB has a significant effect on KP (t = 8.875, p = 0.000). The F test shows that the overall regression model is significant (F = 78.75, p = 0.000). The coefficient of determination (R Square) of 0.562 indicates that 56.2% of the variation in KP can be explained by SCBB, with an Adjusted R Square of 0.557.The conclusion of this study is that Consumer Sentiment towards Sustainable Branding (SCBB) has a positive and significant influence on consumer purchasing decisions (KP) in the retail industry in Bandung City. Digital marketing strategies that focus on sustainable branding are proven to be an important factor influencing consumer purchasing decisions. The results of this study provide insight for retail industry players in designing effective digital marketing strategies to increase consumer purchasing decisions through a sustainable branding approach.